Puccini's Tosca - Illica, Luigi, 1857-1919.; Fisher, Burton D.; Giacosa, Giuseppe, 1847-1906.; Illica, Luigi, 1857-1919.; Illica, Luigi, 1857-1919.; Puccini, Giacomo, 1858-1924.; Sardou, Victorien, 1831-1908. (Coral Gables, Fla. : Opera Journeys, 2002)
Puccini's Tosca is a high-voltage, powerful and sensational opera thriller that is crammed with actoin, intense, and sometimes ferocious, supercharged dramatic confrontations: a true music drama.
Discography: pages 91-96.
Videography: pages 97-100.
Print version record.
Text in Italian with parallel English translation.
eBooks on EBSCOhost
Keywords: Puccini, Giacomo, -- 1858-1924.; Tosca (Puccini, Giacomo); Operas -- Librettos; Opéras -- Livrets; MUSIC -- Genres & Styles -- Opera; Operas -- Librettos